Rapid resolution of acute subdural hematoma: A case report and review of literature - Yadav, Yad Ram; Agarwal, Moneet; Namdev, Hemant; Parihar, Vijay (Indian Journal of Neurotrauma, 2011)
Acute traumatic subdural hematoma is a common condition. Cases of rapid resolution of acute subdural hematoma have seldom been reported in the literature. We are reporting one such case of 53 year-old-male admitted after road traffic accident. Patient became unconscious immediately after the accident. Computed Tomography (CT) done after one hour of accident showed an acute hyperdense subdural hematoma with low density area between skull and hematoma and subarachnoid hemorrhage (SAH). He improved quite rapidly during transportation and became conscious at the time of admission in our hospital. Repeat CT scan done after 7 hours showed marked resolution of hematoma but there was evidence of subarachnoid hemorrhage (SAH). Another CT scan done after 72 hours of injury showed complete resolution of hematoma with evidence of SAH. Possible mechanism of spontaneous resolution of the hematoma in our case was dilution and washing-out of hematoma by the cerebrospinal fluid due to an arachnoid tear. Clinician should suspect possibility of resolving hematoma if CT scan shows presence of SAH and hypodensity between hematoma and skull. Such patients who do not deteriorate while awaiting surgery because of delay due to any reason should get a repeat CT scan before planning any surgical intervention.
Keywords: acute subdural hematoma; traumatic; intracranial subdural hematoma